2020
DOI: 10.1016/j.humpath.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry in the diagnosis and classification of neuroendocrine neoplasms: what can brown do for you?

Abstract: This review is based on a presentation given at the Hans Popper Hepatopathology Society companion meeting at the 2019 United States and Canadian Academy of Pathology Annual Meeting. It presents updates on the diagnosis and classification of neuroendocrine neoplasms, with an emphasis on the role of immunohistochemistry. Neuroendocrine neoplasms often present in liver biopsies as metastases of occult origin. Specific topics covered include 1. general features of neuroendocrine neoplasms, 2. general neuroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 133 publications
(135 reference statements)
5
145
0
5
Order By: Relevance
“…These have become important markers for the diagnosis and follow-up of patients with NENs [20]. Among them, CgA and Syn are considered to be the most important biomarkers for the diagnosis of NENs [21,22]. Our results showed that the positive rates of CgA and Syn in the primary site were 57.5 and 85.4%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…These have become important markers for the diagnosis and follow-up of patients with NENs [20]. Among them, CgA and Syn are considered to be the most important biomarkers for the diagnosis of NENs [21,22]. Our results showed that the positive rates of CgA and Syn in the primary site were 57.5 and 85.4%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the Aperio algorithm for detection of nuclear immunoreactivity involves setting more than 40 different parameters, thus increasing the likelihood of interlaboratory variability in automated measurements of Ki‐67%. Bellizi 55 has proposed that: ‘any discernible Ki‐67 should be counted’, citing Sobecki et al ., 56 who showed Ki‐67 expression varies from cell to cell within a tumour in accordance with the phase of the cell cycle. Given that the cells in a tumour are not synchronised in vivo , these authors conclude that intratumoural heterogeneity in expression and in immunoreactivity is to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these arguments concerning the pathogenesis of mixed tumors are also seen in adrenal or gastroenteropancreatic NENs ( 68–71 ). “Mixed neuroendocrine–non-NENs (MiNENs)” are defined by the association of at least 2 morphologically different neoplastic components, with the requirement that the minor component comprise ≥ 30% of the tumor, which have been introduced in the fifth edition of the WHO classification of the digestive system tumors published in 2019 ( 69 , 70 , 72 ). Many NENs may show evidence of non-neuroendocrine differentiation, whereas many non-neuroendocrine tumors may contain subpopulations of neuroendocrine cells.…”
Section: Discussionmentioning
confidence: 99%